2019
DOI: 10.29317/ejpfm.2019030405
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole capture centers in an irradiated K2SO4-Cu crystal

Abstract: The methods of vacuum-ultraviolet and thermal activation spectroscopy were used to measure the excitation spectra of impurity radiation in the fundamental absorption band of K 2 SO 4-Cu crystals at 15 K and 300 K. An energy transfer was detected from the base to Cu + impurities. The band gap of crystals K 2 SO 4 was estimated. In K 2 SO 4-Cu crystals, recombination radiation bands were detected at 2.95 ÷ 3.0 eV corresponding to electron-hole capture centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Only a few studies have been carried out showing the luminescence properties of SrSO 4 by doping it with rare‐earth elements. [ 13,14,21,22 ] Similarly, few reports are available in the literature on intrinsic recombination luminescence in various alkali metal sulphates [ 23–27 ] and calcium sulphate [ 28,29 ] providing results on defect‐based luminescence having a Stokes shift. Recently, Bao‐gai Zhai et al have also shown intrinsic PL and cyan‐coloured afterglow in undoped SrSO 4 nanoplates on UV excitation due to the presence of defects, mainly due to oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have been carried out showing the luminescence properties of SrSO 4 by doping it with rare‐earth elements. [ 13,14,21,22 ] Similarly, few reports are available in the literature on intrinsic recombination luminescence in various alkali metal sulphates [ 23–27 ] and calcium sulphate [ 28,29 ] providing results on defect‐based luminescence having a Stokes shift. Recently, Bao‐gai Zhai et al have also shown intrinsic PL and cyan‐coloured afterglow in undoped SrSO 4 nanoplates on UV excitation due to the presence of defects, mainly due to oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…During the excitation of pure Na 2 SO 4 − Cu crystals two types of emission appears: intrinsic short-wavelength emission at 3.7-3.8 eV associated with the recombination of electrons with nonequivalently located holes SO − 4 ; recombination emission bands at 3.0-3.1 eV, 2.6-2.7 eV and 2.3-2.4 eV is associated with the formation of electron-hole trapping centers. Earlier, in our works [14][15][16], the nature of the recombination long-wavelength emission bands was purposefully investigated. Based on measurements of the excitation spectra for long-wavelength emission, it is shown that these recombination tunneling emissions arise at electron-hole trapping centers.…”
Section: Introductionmentioning
confidence: 99%
“…increase the concentration of impurity trapping centers. For example, in alkali metal sulfates with an admixture of the Cu + , impurity trapping centers Cu 0 − SO − 4 are created, which are responsible for the formation of an impurity dosimetric TSL peak in TLD dosimeters [14][15][16].…”
Section: Introductionmentioning
confidence: 99%